Removal of Intra-Array Statics in Seismic Arrays Due to Variable Topography and Positioning Errors - Sherif Mohamed Hanafy; Abdullah Al-Mashhor; Abdullatif Abdulrahman Al-Shuhail (Applied Sciences, 2022)
A receiver array is an arrangement of geophones used to enhance the signal-to-noise ratio (S/N) of seismic data. However, deviations from ideal array conditions can lead to the non-optimal performance of the array. This study investigates, quantitatively, the array performance in the presence of topographic variations and positioning errors using 2D seismic data acquired in eastern Saudi Arabia. A receiver array was laid over a sand dune with variable topography underlain by a flat sabkha that has a very shallow water table. The topographic variations and position errors were calculated from Differential Global Positioning System (D-GPS) measurements of source and receiver positions and elevations. The errors in receiver positions, measured relative to the ideal receiver spacing, gave a mean and standard deviation of about 0.35% and 1%, respectively. On the other hand, elevation errors (topographic variations) from a horizontal datum gave a mean and standard deviation of about 25% and 13%, respectively. The ideal array response was found by removing both elevation and position errors. The first-arrival energy of the array was calculated after removal of elevation and position errors separately and compared to the ideal-array energy. Comparison showed a 64% enhancement in the first-arrival energy after correcting for elevation errors alone and almost no enhancement after correcting for position errors alone. The proposed approach can be used to calculate accurate static corrections for seismic reflection processing and to generate high-resolution subsurface images for engineering applications.